Effects and safety of hypertonic saline combined with airway clearance in non-hospitalized children with recurrent wheezing - Vanesa González-Bellido; Verónica Veláz-Baza; Noelia Rama-Suárez; Carmen Jimeno-Esteo; Josep Sirvent-Gomez; Juan Nicolás Cuenca-Zaldívar; Sari Mayorales-lises; Márcio Vinícius Fagundes Donadio; Samuel Fernández-Carnero (World Scientific Publishing, 2023)
Background: The International Study of Wheezing in Infants defines recurrent wheezing as the presence of three or more medically documented episodes of wheezing within one year. To date, there is no evidence on the use of hypertonic saline (HS) combined with airway clearance techniques (ACT) for children with recurrent wheezing treated in an outpatient setting. Therefore, this is the first study to explore the use of such interventions in infants with recurrent wheezing. Objectives: To evaluate the effects and safety of a three-month protocol including HS and ACT for non-hospitalized infants with recurrent wheezing. Methods: Randomized, double-blind, controlled trial, including outpatient infants with recurrent wheezing. Children were randomized to either 3% HS or 0.9% saline groups and were treated with bronchodilator and nebulized with the respective solutions before ACT. The primary outcome was the Wang score. Secondary outcomes included the number of hospitalizations and respiratory crisis, need for rescue medication, and school absences. All variables were measured during the three previous months from inclusion and during intervention period. The study protocol was registered at ClinicalTrials.gov (NCT04331496) on March, 31, 2020. Results: Forty children were included. Regarding immediate effects, significant differences ([Formula: see text]) were found for time, but not for group or interaction (group × time), in all outcome variables (increase in SpO2, decrease in heart and respiratory rate, wheezing episodes, retraction, and Wang score). Comparing the previous three months with the study period, there were significant differences in both groups for the severity of crisis ([Formula: see text]) and medication steps ([Formula: see text]). Conclusion: A three-month protocol including HS and ACT for outpatient infants with recurrent wheezing was safe and reduced morbidity. No differences were found between the use of HS and 0.9% saline.